(untitled) - Hill, Errol G. (Cambridge, 2003)
This definitive history of African-American theatre embraces companies from across the U.S., as well as the anglophone Caribbean and African-American companies touring Europe, Australia and Africa. Representing a catholicity of styles, from African ritual to European forms, amateur to professional, and political nationalism to integration, the volume covers all aspects of performance. It includes minstrel, vaudeville, and cabaret acts, as well as shows written by whites that used black casts.
Keywords: African American theater,American drama,African Americans,Nhà hát Mỹ gốc Phi,Kịch Mỹ,Người Mỹ gốc Phi; History,African American authors,Intellectual life,Lịch sử,Tác gải người Mỹ gốc Phi,Đời sống trí tuệ